Prevalence and functional status of children with complex chronic conditions in Brazilian PICUs during the COVID-19 pandemic - José Colleti, Junior; Arnaldo Prata-Barbosa; Fernanda Lima-Setta; Orlei Ribeiro de Araujo; Nelson K. Horigoshi; Regina Grigolli Cesar; Andreia Aparecida Freitas Souza; Flávia Andrea Krepel Foronda; Carlos Gustavo de Almeida; Lara de Araujo Torreão; Francielly Crestani; Ana Paula de Carvalho Panzeri Carlotti; et al. (Elsevier, 2022)
Objective: The proportion of children with complex chronic conditions is increasing in PICUs around the world. We determined the prevalence and functional status of children with complex chronic conditions in Brazilian PICUs during the COVID-19 pandemic. Methods: The authors conducted a point prevalence cross-sectional study among fifteen Brazilian PICUs during the COVID-19 pandemic. The authors enrolled all children admitted to the participating PICUs with complex chronic conditions on three different days, four weeks apart, starting on April 4th, 2020. The authors recorded the patient's characteristics and functional status at admission and discharge days. Results: During the 3 study days from March to June 2020, the authors enrolled 248 patients admitted to the 15 PICUs; 148 had CCC (prevalence of 59.7%). Patients had a median of 1 acute diagnosis and 2 chronic diagnoses. The use of resources/devices was extensive. The main mode of respiratory support was conventional mechanical ventilation. Most patients had a peripherally inserted central catheter (63.1%), followed by a central venous line (52.5%), and 33.3% had gastrostomy or/and tracheostomy. The functional status score was significantly better at discharge compared to admission day due to the respiratory status improvement. Conclusions: The prevalence of children with CCC admitted to the Brazilian PICUs represented 59.7% of patients during the COVID-19 pandemic. The functional status of these children improved during hospitalization, mainly due to the respiratory component.